Religious Leaders' Perceptions of the Suicide Phenomenon in Kupang City - Lobo, Kayus Mulya A.; Wijaya, R Pasifikus Christa; Aipipidely, Diana (Universitas Nusa Cendana, 2025)
This study aims to understand the perceptions of religious leaders inKupang City towards suicide to see how religious values influence their perspectivesand handling of the issue. The participants in the study numbered three people,consisting of three religions with a majority in Kupang City, namely Catholic,Protestant, and Islam. Using qualitative research methods, data were collectedthrough semi-structured interviews and analyzed using thematic analysis. Theresults of this study indicate that religious leaders in Kupang City understand suicideas an act that does not follow religious teachings and generally occurs due to severelife pressures. They show deep concern and want to be directly involved in suicideprevention efforts, such as providing spiritual support and encouragement, helpingemotionally, and educating the community to be more aware of the importance ofmaintaining mental health.